Analisis Kehilangan Gaya Prategang Girder Pada Jembatan Proyek Pembangunan Jalan Tol Tebing Tinggi – Inderapura - Nur Purnama Sari; Irwan Irwan; Hermansyah Hermansyah (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2022)
Currently, the construction of toll roads in several regions of Indonesia is being carried out. One of them is the construction of the Tebing Tinggi-Inderapura Toll Road. In this project there are several bridge constructions as a link between roads or as a pedestrian bridge. This bridge uses prestressed beams in which there are steel wires. The steel wire is tensioned by pulling it using a hydraulic jack. When stress is applied, the beam loses its prestressing force. The purpose of this study was to determine the percentage loss of prestressing forces that occurred in the bridge beam. Loss of prestressing force must not exceed the maximum that has been determined. There is some loss of prestressing force which is taken into account. Short-term prestress losses include elastic shortening of the concrete, friction along the tendons and anchor slippage. Furthermore, the loss of long-term prestressing forces is creep in steel, shrinkage in concrete and relaxation of steel. After all the loss of prestressing force is calculated, the total loss of prestressing force is 21.62%. To find out the maximum percentage of loss of prestressing force using calculations from the book Design of Prestressed Concrete Structures by T. Y. Lin H. Burns with the formula Pe/Ac and the value is 8.98 MPa. Where 8.98 MPa is 25%, so 21.62% is smaller than 25%, so it is still safe. In addition, an implementation method for installing girders on bridges is introduced..